Information System for Predicting Warehouse Stock and Utilities (Case Study: PT KERAMIK XYZ) - Pramitarini, Yushintia; Saputra, Pramana Yoga; Putri, Alindya Kirana (Jurnal IPTEK, 2021)
PT KERAMIK XYZ is one of the companies engaged in the production of ceramics. The company sometimes subjected to declining wall tiles on the market and at warehouses where wall ceramic stocks are sometimes subjected to buildup. Therefore, the research of "Information System Prediction Stock and Warehouse Utility" uses the Fuzzy Time Series Markov Chain method and Fuzzy Mamdani Method. So that the problem of ceramic wall stock and the layout of the placement of ceramic wall stock in the warehouse does not occur again and can be resolved. In the Fuzzy Time Series Markov Chain method, the calculation of prediction results of ceramic stocks of the Base Tile dCaliza Valle type results in forecasting values of (0, 717, 483, 483), then by means of the MAPE (Mean Absolute Percent Error) test method produces an error percentage of 13%. The results of the calculation of the level of accuracy are good and can be used in this case study. So, the results of the calculation of the level of accuracy are good and can be used in this case study. Then for the results of the prediction of the layout of the ceramic stock placement in the warehouse using the Fuzzy Mamdani method get an accurate calculation of 22%.